Public involvement in research: assessing impact through a realist evaluation - David Evans; Jane Coad; Kiera Cottrell; Jane Dalrymple; Rosemary Davies; Christine Donald; Vito Laterza; Amy Long; Amanda Longley; Pam Moule; Katherine Pollard; Jane Powell; et al. (National Institute for Health Research, 2014)
Background: This study was concerned with developing the evidence base for public involvement in research in health and social care. There now is significant support for public involvement within the National Institute for Health Research, and researchers applying for National Institute for Health Research grants are expected to involve the public. Despite this policy commitment, evidence for the benefits of public involvement in research remains limited. This study addressed this need through a realist evaluation. Aim and objectives: The aim was to identify the contextual factors and mechanisms that are regularly associated with effective public involvement in research. The objectives included identifying a sample of eight research projects and their desired outcomes of public involvement, tracking the impact of public involvement in these case studies, and comparing the associated contextual factors and mechanisms. Design: The research design was based on the application of realist theory of evaluation, which argues that social programmes are driven by an underlying vision of change - a 'programme theory' of how the intervention is supposed to work. The role of the evaluator is to compare theory and practice. Impact can be understood by identifying regularities of context, mechanism and outcome. Thus the key question for the evaluator is 'What works for whom in what circumstances . . . and why?' (Pawson R. The Science of Evaluation. London: Sage; 2013). We therefore planned a realist evaluation based on qualitative case studies of public involvement in research. Setting and participants: Eight diverse case studies of research projects in health and social care took place over the calendar year 2012 with 88 interviews from 42 participants across the eight studies: researchers, research managers, third-sector partners and research partners (members of the public involved in research). Results: Case study data supported the importance of some aspects of our theory of public involvement in research and led us to amend other elements. Public involvement was associated with improvements in research design and delivery, particularly recruitment strategies and materials, and data collection tools. This study identified the previously unrecognised importance of principal investigator leadership as a key contextual factor leading to the impact of public involvement; alternatively, public involvement might still be effective without principal investigator leadership where there is a wider culture of involvement. In terms of the mechanisms of involvement, allocating staff time to facilitate involvement appeared more important than formal budgeting. Another important new finding was that many research proposals significantly undercosted public involvement. Nurturing good interpersonal relationships was crucial to effective involvement. Payment for research partner time and formal training appeared more significant for some types of public involvement than others. Feedback to research partners on the value of their contribution was important in maintaining motivation and confidence. Conclusions: A revised theory of public involvement in research was developed and tested, which identifies key regularities of context, mechanism and outcome in how public involvement in research works. Implications for future research include the need to further explore how leadership on public involvement might be facilitated, methodological work on assessing impact and the development of economic analysis of involvement. Funding details: The National Institute for Health Research Health Service and Delivery programme.